Inhibition of a Snake Venom Metalloproteinase by the Flavonoid Myricetin (2018)
ABSTRACT: Most of the snakebite envenomations in Central and South America are caused by species belonging to Bothrops genus. Their venom is composed mainly by zinc-dependent metalloproteinases, responsible of the hemorrhage characteristic of these envenomations. The aim of this study was to determine the inhibitory ability of ten flavonoids on the in-vitro proteolytic activity of Bothrops atrox venom and on the hemorrhagic, edema-forming and myonecrotic activities of Batx-I, the most abundant metalloproteinase isolated from this venom. Myricetin was the most active compound, exhibiting an IC50 value of 150 µM and 1021 µM for the inhibition of proteolytic and hemorrhagic activity, respectively. Independent injection experiments, with a concentration of 1600 µM of myricetin administered locally, immediately after toxin injection, demonstrated a reduction of 28 ± 6% in the hemorrhagic lesion. Additionally, myricetin at concentrations 800, 1200 and 1600 µM promoted a reduction in plasma creatine kinase activity induced by Batx-I of 21 ± 2%, 60 ± 5% and 63 ± 2%, respectively. Molecular dynamics simulations coupled with the adaptive biasing method suggest that myricetin can bind to the metalloproteinase active site via formation of hydrogen bonds between the hydroxyl groups 3’, 4’ and 5’ of the benzyl moiety and amino acid Glu143 of the metalloproteinase. The hydroxyl substitution pattern of myricetin appears to be essential for its inhibitory activity. Based on this evidence, myricetin constitutes a candidate for the development of inhibitors to reduce local tissue damage in snakebite envenomation.